Строение гениталий самцов и географическое распространение палеарктических комаров группы Aedes communis - Данилов, В.Н. (Вестник зоологии, 1984)
The Structure of the Male Genitalia and Geographic Distribution of the Palearctic
Mosquitoes of Aeades communis Group (Diptera, Culicidae). Danilov V. N.— Vestn.
z00l., 1984, No. 2. The reliable characters of the male genitalia allowed distinguishing
Aedes communis and Ae. pionips, up to present considered to be undistinguishable: length
and shape of the setae on the basistyle apical lobe and shape of the claspette filament
apex. A correct figure of Ae. rempeli male genitalia and a map of its occurrence in the

Palearctic region are given.